2008
DOI: 10.1002/hc.20394
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis of trisubstituted alkenes containing (Z)‐allylthio units from the acetates of Baylis–Hillman adducts

Abstract: A series of trisubstituted alkenes containing (Z)-allylthio moieties as key structural units, that is, sodium (Z)-allyl thiosulfates, symmetrical di(Z-allyl) sulfides, and di(Z-allyl) disulfides, unsymmetrical diallyl sulfides were prepared in moderate to good yields via chemical transformations from the acetates of Baylis-Hillman adducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Very recently, Reddy and co-workers 624 used hydroxylamide derivatives as the aminoxy-equivalent nucleophiles in palladium-catalyzed addition to Baylis-Hillman acetates in acetonitrile to produce the required products in good yields Zhang and co-workers [626][627][628] have transformed acetates of Baylis-Hillman adducts into sodium (Z)-allylthiosulfates (323) in high isolated yields via the treatment with sodium thiosulfate in methanol (eq 92). These allyl thiosulfates generated in situ were transformed into unsymmetrical diallylsulfides via the treatment with allyl bromide in the Later on, Lee and co-workers 629 reported synthesis of symmetric diallyl disulfides from the Baylis-Hillman acetates via treatment with thioacetic acid followed by the reaction of the resulting allylthio acetates with sodium azide or sodium methoxide (Scheme 205).…”
Section: Applications Of Baylis-hillman Adducts and Their Derivatives...mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Reddy and co-workers 624 used hydroxylamide derivatives as the aminoxy-equivalent nucleophiles in palladium-catalyzed addition to Baylis-Hillman acetates in acetonitrile to produce the required products in good yields Zhang and co-workers [626][627][628] have transformed acetates of Baylis-Hillman adducts into sodium (Z)-allylthiosulfates (323) in high isolated yields via the treatment with sodium thiosulfate in methanol (eq 92). These allyl thiosulfates generated in situ were transformed into unsymmetrical diallylsulfides via the treatment with allyl bromide in the Later on, Lee and co-workers 629 reported synthesis of symmetric diallyl disulfides from the Baylis-Hillman acetates via treatment with thioacetic acid followed by the reaction of the resulting allylthio acetates with sodium azide or sodium methoxide (Scheme 205).…”
Section: Applications Of Baylis-hillman Adducts and Their Derivatives...mentioning
confidence: 99%
“…Zhang and co-workers have transformed acetates of Baylis−Hillman adducts into sodium ( Z )-allylthiosulfates ( 323 ) in high isolated yields via the treatment with sodium thiosulfate in methanol (eq ). These allyl thiosulfates generated in situ were transformed into unsymmetrical diallylsulfides via the treatment with allyl bromide in the presence of indium.…”
Section: Applications Of Baylis−hillman Adducts and Their Derivatives...mentioning
confidence: 99%
“…To find the suitable reaction conditions for the proposed thioannulation, MBH acetate 1a , derived from the reaction of 3-phenylpropiolaldehyde with methyl acrylate, was employed as a model substrate. Initially, compound 1a was treated with Na 2 S·9H 2 O (1 equiv) in CH 2 Cl 2 at room temperature, wherein the formation of a ( Z )-dialkyl thio-ether 3 was observed in 94% yield (entry 1, Table ). , Next, few other thio-reagents were examined, and it was found that the reaction of 1a with KSAc in the presence of K 2 CO 3 produced the thiophene 2a in 94% yield (entry 6, Table ). In the absence of K 2 CO 3 , the reaction of 1a with KSAc provided the ( Z )-allylic thioacetate 4 (entry 2, Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…[16] These methods generally either involve multiple steps and provide low yields or employ starting materials with limited availability. [16] These methods generally either involve multiple steps and provide low yields or employ starting materials with limited availability.…”
Section: Resultsmentioning
confidence: 99%